Namibia : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Namibia. (IMF Staff Country Reports; Country Report ;, 2018)
This 2017 Article IV Consultation highlights that Namibia's economy has reached a turning point with ending of temporary expansionary factors. GDP sharply decelerated in 2016 and contracted in 2017 as construction in the mining sector came to an end and the government began consolidating. With the economy contracting and Southern Africa Customs Union's receipts temporarily increasing, the current account balance improved significantly. The outlook remains positive with considerable vulnerabilities and risks. Growth is projected to resume in 2018, as mining production ramps up, construction activity stabilizes and manufacturing recovers, before converging to a long-term rate of about 3.5 percent, below the average of recent years.